Chemical and physical changes during seawater flow through intact dunite cores: An experimental study at 150–200 °C. (1st October 2017) - Luhmann, Andrew J.; Tutolo, Benjamin M.; Bagley, Brian C.; Mildner, David F.R.; Scheuermann, Peter P.; Feinberg, Joshua M.; Ignatyev, Konstantin; Seyfried, William E.
Abstract: Two flow-through experiments were conducted to assess serpentinization of intact dunite cores. Permeability and fluid chemistry indicate significantly more reaction during the second experiment at 200 °C than the first experiment at 150 °C. Permeability decreased by a factor of 2.4 and 25 during the experiments at 150 and 200 °C, respectively. Furthermore, hydrogen and methane concentrations exceeded 600 μmol/kg and 300 μmol/kg during the 200 °C experiment, and were one and two orders of magnitude higher, respectively, than the 150 °C experiment. Fe K-edge X-ray absorption near edge structure analyses of alteration minerals demonstrated Fe oxidation that occurred during the 200 °C experiment. Vibrating sample magnetometer measurements on post-experimental cores indicated little to no magnetite production, suggesting that the hydrogen was largely generated by the oxidation of iron as olivine was converted to ferric iron (Fe(III)) serpentine and/or saponite. Scanning electron microscopy images suggested secondary mineralization on the post-experimental core from the 200 °C experiment, portraying the formation of a secondary phase with a honeycomb-like texture as well as calcite and wollastonite. Scanning electron microscopy images also illustrated dissolution along linear bands through the interiors of olivine crystals, possibly along pathways with abundant fluid inclusions. Energy dispersive X-ray spectroscopy identified Cl uptake in serpentine, while Fourier transform-infrared spectroscopy suggested the formation of serpentine, saponite, and talc. However, no change was observed when comparing pre- and post-experimental X-ray computed tomography scans of the cores. Furthermore, (ultra) small angle neutron scattering datasets were collected to assess changes in porosity, surface area, and fractal characteristics of the samples over the ≈ 1 nm- to 10 μm-scale range. The results from the 200 °C post-experimental core generally fell within the range of values for the two pristine samples and the 150 °C post-experimental core that underwent negligible reaction, indicating that any change from reaction was smaller than the natural variability of the dunite. Even though there was little physical evidence of alteration, the initial stage of serpentinization at 200 °C was sufficiently significant to have a dramatic effect on flow fields in the core. Furthermore, this experiment generated significant dissolved hydrogen concentrations while simulating open system dynamics. Even though open systems prevent elevated hydrogen concentrations due to continual loss of hydrogen, we speculate that this process is responsible for stabilizing ferric Fe-rich serpentine in nature while also oxidizing more ferrous iron (Fe(II)) and cumulatively generating more hydrogen than would be possible in a closed system.